Simultaneous determination of candesartan and hydrochlorothiazide in human plasma by LC-MS/MS (Brazilian Journal of Pharmaceutical Sciences, 2018)
A simple, sensitive, rapid and highly efficient LC-MS/MS method was developed for the determination of Candesartan and Hydrochlorothiazide simultaneously in human plasma. The method employed Zorbax eclipse C18 (150 X 4.6 mm, 5µ) column using acetate buffer: acetonitrile (25:75%, v/v) as the mobile phase. The mobile phase flow rate is 1 mL/min which was delivered into the mass spectrometer electron spray ionization chamber. The Liquid/liquid extraction procedure was used in the method for the extraction of analytes. The chromatograph was attached to a negative ion mode tandem mass spectrometer and the method was validated for all the parameters as per the guidelines of US-FDA. The ions were detected in multiple reaction monitoring mode and the transitions are m/z 439.00®309.10 and 295.80®268.80 for candesartan and hydrochlorothiazide respectively. Isotopic standards were used as internal standards for effective recovery of the analytes. The drugs were analyzed over a calibration range of 1.027-302.047 ng/mL for candesartan and 1.044-306.945 ng/mL for hydrochlorothiazide respectively with regression coefficient greater than 0.99. The mean extraction recoveries are 96.95±5.61 and 100.55±4.82 for candesartan and hydrochlorothiazide respectively. The precision and accuracy values for all the studies were within the range of ≤15% and 85-115%. The performed stability studies indicate that the developed method is stable in plasma for 15 h at room temperature (bench top); 52 h (in injector); for 112 days at -70 ºC for long term stability; five successive freeze and thaw cycles. The developed method could be successfully employed for the determination of selected drugs in biological samples.